Akuntabilitas Pengelolaan Keuangan Desa Berdasarkan Filosofi Tri Hita Karana di Desa Buduk, Kecamatan Mengwi, Kabupaten Badung - Astri Pramitari, I Gusti Ayu; Nurhayanti, Ketut (E-Jurnal Akuntansi; Vol 30 No 11 (2020)DO - 10.24843/EJA.2020.v30.i11.p18, 2020)
This research was conducted to understand financial management in Buduk Village based on the Tri Hita Karana philosophy. This research uses qualitative approach with ethnomethodology method. The data was collected by interview, observation, and documentation. The results of this study indicate that the Buduk Village Government has implemented accountable financial management based on the Tri Hita Karana philosophy, which can be seen from accountability to God (Parahyangan), accountability to the community (Pawongan) and accountability to the environment (Palemahan). Keywords: Accountability; Financial Reporting; Village Fund;  Tri Hita Karana.